2011
DOI: 10.1093/infdis/jir689
|View full text |Cite
|
Sign up to set email alerts
|

Identification of H5N1-Specific T-Cell Responses in a High-risk Cohort in Vietnam Indicates the Existence of Potential Asymptomatic Infections

Abstract: This is the first report of ex vivo H5 HA-specific T-cell responses in a healthy but H5N1-exposed population. Our results indicate that the presence of H5N1-specific T cells could be an additional diagnostic tool for asymptomatic H5N1 infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…Collection of serum closer to the time of exposure to confirmed HPAI H5N1 virus outbreaks among poultry and at multiple time points would have enabled us to better assess the kinetics of the HPAI H5N1 virus neutralizing antibody response over time among farm and market workers. Other methods to assess the cellular immune response such as measuring H5N1-specific T-cell responses might help identify prior HPAI H5N1 virus infections that resulted in asymptomatic or mild illness [28]. Exposure to HPAI H5N1 virus in poultry workers can potentially include self-inoculation of mucous membranes (including conjunctivae) of the respiratory tract after direct contact with poultry or surfaces contaminated with feces, internal organ tissues, or poultry blood; or through inhalation of large or small droplets that are aerosolized such as those generated through slaughtering, defeathering, or evisceration [29].…”
Section: Discussionmentioning
confidence: 99%
“…Collection of serum closer to the time of exposure to confirmed HPAI H5N1 virus outbreaks among poultry and at multiple time points would have enabled us to better assess the kinetics of the HPAI H5N1 virus neutralizing antibody response over time among farm and market workers. Other methods to assess the cellular immune response such as measuring H5N1-specific T-cell responses might help identify prior HPAI H5N1 virus infections that resulted in asymptomatic or mild illness [28]. Exposure to HPAI H5N1 virus in poultry workers can potentially include self-inoculation of mucous membranes (including conjunctivae) of the respiratory tract after direct contact with poultry or surfaces contaminated with feces, internal organ tissues, or poultry blood; or through inhalation of large or small droplets that are aerosolized such as those generated through slaughtering, defeathering, or evisceration [29].…”
Section: Discussionmentioning
confidence: 99%
“…9,16 Two recent studies among the 18 non-clade 0 studies reported higher rates of asymptomatic H5N1 exposure than others: one among inhabitants of rural Thai villages where H5N1 was endemic, where 5.6% were found to be seropositive; and another in Vietnam that reported 5% of a high-risk cohort were seropositive. 10,16 In the Thai study, seropositivity was associated with lack of indoor waterbut not poultry contact-suggesting the possibility of a water-related route of exposure. The Vietnam study, in addition to using traditional hemagglutination inhibition (HAI) serology test assays, employed an ELISPOT assay to evaluate T-cell responses to H5 antigens.…”
Section: Seroepidemiologic Studiesmentioning
confidence: 92%
“…Some tests are plagued by false positives, others by false negatives; some may cross-react with other influenza viruses, and there may be limited correlation among the different tests. 10 In some studies, there seemed to be an association between seropositivity and exposure to untreated water, which may reflect the fact that H5N1 has been found in bodies of water contaminated by infected ducks. 9,16 Two recent studies among the 18 non-clade 0 studies reported higher rates of asymptomatic H5N1 exposure than others: one among inhabitants of rural Thai villages where H5N1 was endemic, where 5.6% were found to be seropositive; and another in Vietnam that reported 5% of a high-risk cohort were seropositive.…”
Section: Seroepidemiologic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In some fatal cases, necropsies have detected high levels of virus in the blood and non-pulmonary tissues; gastrointestinal disease, including vomiting and diarrhea, and involvement of the central nervous system are less common. Mild or asymptomatic infections also occur (Powell et al, 2012; Le et al, 2013; Gomaa et al, 2014; Morens and Taubenberger, 2014) .…”
Section: Studies Of Avian Influenza In Nhpsmentioning
confidence: 99%